1997
DOI: 10.3109/00365519709055286
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-labelled immunoglobulin scintigraphy in arthritis: an analysis of synovial fluid activity

Abstract: The distribution of 99mTc-labelled human polyclonal non-specific immunoglobulin G (HIG) in the synovial fluid was studied in 14 patients with rheumatoid and non-rheumatoid arthritides. Analysis included the determination of the total activity per ml synovial fluid 6 h post-injection (p.i.) of the tracer as well as of the protein- and cell-bound fractions. At 6 h p.i., > 60% of the injected dose remained in plasma as protein-bound radioactivity. Values in the synovial fluid ranged between 0.001 and 0.009% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Specific or non-specific endocytosis of the protein by synoviocytes were considered as a potential mechanism of uptake 9, 13, 15, 24 but recent studies confirmed the lack of a significant role of cellular binding in determining the accumulation of 99m Tc-IgG in inflamed tissues. 9,16,17 The accumulation in sites of synovial inflammation seems to depend upon endothelial permeability, increased blood flow and probably increased immune response as stated by Jamar et al 16 In conclusion, our data indicate that 99m Tc-IgG scintigraphy can be appropriate for detecting inflammation of peripheral joints and can be used to establish the extent of arthritis in patients with inflammatory bowel disease. Further studies are needed to elucidate the specific mechanism behind the uptake in inflamed joints of patients with enteropathic arthropathies.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Specific or non-specific endocytosis of the protein by synoviocytes were considered as a potential mechanism of uptake 9, 13, 15, 24 but recent studies confirmed the lack of a significant role of cellular binding in determining the accumulation of 99m Tc-IgG in inflamed tissues. 9,16,17 The accumulation in sites of synovial inflammation seems to depend upon endothelial permeability, increased blood flow and probably increased immune response as stated by Jamar et al 16 In conclusion, our data indicate that 99m Tc-IgG scintigraphy can be appropriate for detecting inflammation of peripheral joints and can be used to establish the extent of arthritis in patients with inflammatory bowel disease. Further studies are needed to elucidate the specific mechanism behind the uptake in inflamed joints of patients with enteropathic arthropathies.…”
Section: Discussionsupporting
confidence: 70%
“…11-13, 15, 20, 22 In the previous studies 99m Tc-IgG scintigraphy was found to be 85% sensitive in detecting synovitis for histological findings and 65% sensitive in detecting clinical findings. 16,22 Berna et al 13 compared conventional bone scan and 99m Tc-IgG scintigraphy in 18 RA patients to assess the Fig. 3 The correlation between total tenderness and total 99m Tc-IgG scintigraphic scores ( p < 0.001, r = 0.79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the last two decades, several studies have aimed to assess the degree of arthritis intensity with scintigraphic approaches. With techniques such as targeted immunoscintigraphy, the presence of relevant molecules can be highlighted by radiolabeled mAbs [4,19,20]. On the basis of the given amount of these relevant molecules involved in the pathophysiology of RA, it allows better staging of the disease and might provide a possibility to perform "evidence-based biologic therapy" for arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The scintigraphic detection of these radiolabeled mAbs allows direct visualization of the synovitis of RA. The combination of the assessment of disease-specific cellular biomarkers directly in the joint and noninvasive high-resolution in vivo imaging techniques, such as immunoscintigraphy or immuno-positron-emission tomography (PET), are suitable approaches to determine alterations in the joints and hence offer valuable tools for sensitive and specific diagnosis in RA [4-7]. …”
Section: Introductionmentioning
confidence: 99%